2014
DOI: 10.3390/toxins6092612
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxins Enhance Statin-Induced Cytotoxicity in Differentiated Human Rhabdomyosarcoma Cells

Abstract: The risk of myopathy and rhabdomyolysis is considerably increased in statin users with end-stage renal failure (ESRF). Uremic toxins, which accumulate in patients with ESRF, exert cytotoxic effects that are mediated by various mechanisms. Therefore, accumulation of uremic toxins might increase statin-induced cytotoxicity. The purpose of this study was to determine the effect of four uremic toxins—hippuric acid, 3-carboxy-4-methyl-5-propyl-2-furanpropionate, indole-3-acetic acid, and 3-indoxyl sulfate—on statin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…These concentrations have been selected based on a review of literature that described the in vitro experiments of statin-induced myotoxicity. 49 , 50 , 51 , 52 , 53 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…These concentrations have been selected based on a review of literature that described the in vitro experiments of statin-induced myotoxicity. 49 , 50 , 51 , 52 , 53 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…To determine if metabolic intermediates of the mevalonate pathway or LDL treatment revert the cells’ atorvastatin-sensitive phenotype, the statin-sensitive cancer cell line HOP-92 was seeded in 12-well plates at a density of 1 × 10 5 cells/mL (1 mL/well), incubated overnight, and then treated with 10 μM atorvastatin and various concentrations of R-mevalonic acid (10–50 μM; Sigma-Aldrich, St. Louis, MO), ubiquinone (25–200 μM; Wako, Osaka, Japan), dolichol (75–300 μM; Avanti Polar Lipids, Alabaster, AL), squalene (10–100 μM; Wako), FPP (1–25 μM; Echelon, Salt Lake City, UT), GGPP (1–25 μM; Sigma-Aldrich), or LDL (50–200 μg/mL; Alfa Aesar, Ward Hill, MA) for 48 hours. We chose the doses of each substrate according to published references [ 53 , 54 ]. In select experiments, we photographed these cells with a phase-contrast microscope to capture any morphological changes.…”
Section: Methodsmentioning
confidence: 99%
“…We had previously shown that statin-induced cytotoxicity in differentiated RD cells was augmented by pre-treatment with uremic toxins—hippuric acid, 3-carboxy-4-methyl-5-propyl-2-furanpropionate, indole-3-acetic acid, and 3-indoxyl sulfate, whereas cisplatin-induced cytotoxicity was not affected by pre-treatment with uremic toxins [ 6 ]. In this study, simvastatin-induced apoptosis and cytotoxicity was greater in US cells than in NS cells ( Table 1 and Figure 1 ), and here, we found that simvastatin-induced cytotoxicity was similarly augmented in US cells.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, cytotoxicity associated with losartan and cisplatin was lower in US cells than NS cells ( Table 1 ). The effect of long-time exposed with US on cisplatin-induced cytotoxicity in RD cells was different from effect of pre-treatment with uremic toxins [ 6 ]. It is possible that the decrease in cisplatin-induced cytotoxicity in US cells was due to serum components apart from uremic toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation